2015
DOI: 10.1007/s11626-015-9934-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleostemin exerts anti-apoptotic function via p53 signaling pathway in cardiomyocytes

Abstract: Cardiomyocytes apoptosis following reperfusion injury causes irreversible damage to cardiac function. Understanding the mechanisms underlying cardiomyocytes death under these conditions can be helpful to identify strategies to abrogate such detrimental effects. Stem cell-specific proteins and regulatory pathways become important in understanding reparative processes in the myocardium. One such regulatory protein named nucleostemin (NS) has vital roles in cardiac ischemia. Although the relationship between NS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[ 37 ] Research has shown that hypoxia may require increased apoptosis of cardiomyocytes via the activated p53 signaling pathway. [ 38 ] The previous study of our research group showed that expression levels of HIF-1α and apoptosis cells were significantly increased in the POP group. [ 39 ] Therefore, HIF-1α may promote fibroblast apoptosis by activating the p53 signaling pathway, and then reducing the production of collagen.…”
Section: Discussionmentioning
confidence: 96%
“…[ 37 ] Research has shown that hypoxia may require increased apoptosis of cardiomyocytes via the activated p53 signaling pathway. [ 38 ] The previous study of our research group showed that expression levels of HIF-1α and apoptosis cells were significantly increased in the POP group. [ 39 ] Therefore, HIF-1α may promote fibroblast apoptosis by activating the p53 signaling pathway, and then reducing the production of collagen.…”
Section: Discussionmentioning
confidence: 96%
“…Bcl-2 inhibits the activation of the upstream caspase protease by interfering with release of cytochrome c, result in inhibition cell apoptpsis [ 30 ]. As a composition of the ion channel on the mitochondrial membrane, Bax protein allows cytochrome c to pass through the mitochondrial membrane, activating caspase-9 further activating caspase-3, thus resulting in cell apoptosis [ 31 ]. Procaspase-9, an initiator caspase in the mitochondrial pathway, is recruited and activated by the apoptosome leading to downstream casepase-3 processing [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 blocks the activation of the upstream caspase protease by interfering with the release of cytochrome c, thus inhibiting cell apoptosis (24). As a composition of the ion channel on the mitochondrial membrane, Bax protein allows cytochrome c to pass through the mitochondrial membrane, activating caspase-9, and further activating caspase-3, thus resulting in cell apoptosis (9). The results revealed that si-caspase-2 also reduced the effects of iodine-131-reduced cell proliferation and induced apoptosis in human cardiac muscle cells through the t-BID/cytochrome c/ caspase-3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 gene expression can block the p53-induced cell apoptosis, which is independent of changes in p53 expression and its location in the nucleus; in addition, it can inhibit the bax transcription of p53 (7,8). Bcl-2 is an important anti-apoptotic factor (9).…”
Section: Introductionmentioning
confidence: 99%